MEMBANGKITKAN JIWA NASIONALISME GENERASI MUDA MELALUI NILAI-NILAI PERJUANGAN BANGSA - Djoko Sutanto; Samsi; Maria Sri Widyastuti; Pramudita Kusuma Putri (Fakultas Ekonomi Universitas Surakarta, 2024)
Abstract The activity with the theme of awakening a sense of nationalism in the younger generation through socializing the values ​​of the nation's struggle was carried out in the form of a workshop intended for members of the youth organization